Exploring New Methods for Measuring Hospital Performance and Quality of Care for More Effective Strategic Planning: A Systematic Review - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Dimyati, Ferry; Sandi, Ghaniy Prima (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Measuring hospital performance and quality of care is crucial for strategic planning to improve patient outcomes. However, there is no consensus on the most effective measurement approach. To explore new methods for measuring hospital performance and quality of care and identify their use in strategic planning. A systematic literature review was conducted using Scopus and Semantic Scholar databases for studies published between 2019-2024. Innovative approaches identified include federated causal inference, comprehensive efficiency index, multidimensional quality assessments, balanced scorecard method, electronic clinical quality measures, and programmatic quality measures. These methods provide comprehensive performance data while addressing challenges like data privacy. New measurement methods can generate valuable data for strategic planning in hospitals. Implementation should be tailored to specific contexts and can lead to more effective planning and improved patient outcomes.